The efficacy and immune-mediated safety of PD-1/PD-L1 combined with neoadjuvant chemotherapy in triple-negative breast cancer: a meta-analysis - Yan, Xiao; Lv, Qi; Wu, Jiangzhuo; Fang, Jiang; Peng, Lin; Zhao, Xiaobo (Frontiers in Oncology, 2025)
BackgroundThe efficacy and immune-mediated safety of PD-1/PD-L1 inhibitors in triple-negative breast cancer (TNBC) remain controversial. Given TNBC’s aggressive biology and poor prognosis, definitive evidence is urgently needed. We performed this meta-analysis to comprehensively assess the benefits and safety of these inhibitors by examining clinical trial data for TNBC.MethodsUp until October 25, 2024, a thorough search was done in the PubMed, Embase, and Cochrane databases to find research assessing PD-1/PD-L1 inhibitors in treating TNBC. This study ultimately included 8 randomized controlled trials involving 5,512 patients. Pathological complete response (pCR), progression-free survival (PFS), overall survival (OS), event-free survival (EFS), and immune-related adverse events (irAEs) were among the primary objectives, which defined as adverse drug reactions affecting various organ systems due to immune system activation, were graded according to CTCAE v5.0 criteria.ResultsThe combination of PD-1/PD-L1 inhibitors with neoadjuvant chemotherapy significantly increased pCR rates by 77% compared to chemotherapy alone (OR=1.77, 95% CI: 1.28-2.45, P<0.01). Subgroup analyses indicated that the benefit of pCR was more evident in patients with lymph node positivity(OR=2.57,95% CI:1.76–3.75, P < 0.01). For EFS, the integration of immune checkpoint inhibitors(ICIs) combination therapy decreased the possibility of events by 35% (HR=0.65,95%CI:0.54–0.80, P< 0.01), with notable benefits observed in earlier-stage (T1-T2) patients(HR= 0.53, 95%CI:0.40–0.70, P < 0.01). Similarly, PFS was improved in the experimental group for both ITT (HR=0.79,95% CI, 0.71–0.88, P<0.01) and PD-L1 positive populations (HR=0.71,95%CI:0.63–0.81, P < 0.01). However, the incidence of irAEs was significantly higher in the ICIs group compared to the neoadjuvant chemotherapy group (OR=2.77,95% CI:1.93–3.96, P < 0.01).ConclusionWith lymph node status acting as a crucial predictor, the combination of PD-1/PD-L1 inhibitors and neoadjuvant chemotherapy dramatically improves pCR and EFS in TNBC. Additionally, it improves OS and PFS, although at the cost of an increased incidence of irAEs. These findings offer insightful information for upcoming clinical trial designs, economic evaluations, and clinical decision-making in TNBC treatment.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025640551.